Molecular Targets of Ascochlorin and Its Derivatives for Cancer Therapy - Min-Wen, J.; Yan-Jiang, B.; Mishra, S.; Dai, X.; Magae, J.; Shyh-Chang, N.; Kumar, Alan Prem; Sethi, G. (2017)
© 2017 Elsevier Inc. Cancer is an extremely complex disease comprising of a multitude of characteristic hallmarks that continue to evolve with time. At the genomic level, random mutations leading to deregulation of diverse oncogenic signal transduction cascades and polymorphisms coupled with environmental as well as life style-related factors are major causative agent contributing to chemoresistance and the failure of conventional therapies as well as molecular targeted agents. Hence, there is an urgent need to identify novel alternative therapies based on alternative medicines to combat this dreaded disease. Ascochlorin (ASC), an isoprenoid antibiotic isolated initially from the fermented broth of Ascochyta viciae, and its synthetic derivatives have recently demonstrated substantial antineoplastic effects in a variety of tumor cell lines and mouse models. The major focus of this review article is to briefly analyze the chemopreventive as well as therapeutic properties of ASC and its derivatives and to identify the multiple molecular targets modulated by this novel class of anticancer agent.